2016
DOI: 10.1016/j.imr.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-care use patterns in the UK, US, Australia, and Japan: a multinational web-based survey

Abstract: BackgroundThe trend toward patient- or consumer-centered healthcare has been accelerated by advances in technology, consumer empowerment, and a shift from infectious to chronic diseases. The purpose of this study was to examine the growing self-care market by analyzing self-care patterns.MethodsWe conducted a cross-sectional, web-based survey involving adults from nine major cities in the UK, the USA, Australia, and Japan. This study examined the extent and frequency of self-care, self-care expenditure, source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Haug et al (1991) found that Japanese elders showed a lower desire for their doctors to provide them with health information and less preference for care by physicians than American cohorts. This finding is further supported by a recent study by Mun et al (2016) who compared and contrasted self-care patterns in the US, UK, Australia and Japan. Lock (1993) found in the 1990s, few Japanese women sought doctors' advice for their menopausal symptoms compared to American cohorts who were encouraged to undergo Hormone Replacement Therapy (HRT) by their doctors.…”
Section: Self-care In the Context Of Anti-ageing Medicinesupporting
confidence: 76%
See 2 more Smart Citations
“…Haug et al (1991) found that Japanese elders showed a lower desire for their doctors to provide them with health information and less preference for care by physicians than American cohorts. This finding is further supported by a recent study by Mun et al (2016) who compared and contrasted self-care patterns in the US, UK, Australia and Japan. Lock (1993) found in the 1990s, few Japanese women sought doctors' advice for their menopausal symptoms compared to American cohorts who were encouraged to undergo Hormone Replacement Therapy (HRT) by their doctors.…”
Section: Self-care In the Context Of Anti-ageing Medicinesupporting
confidence: 76%
“…High prevalence of CAM use among the Japanese has been also reported in several studies (Flaherty et al 2001, Lee et al 2004, Mun et al 2016, Yamashita et al 2002. CAM includes dietary supplements, Kampo (Japanese traditional herbal medicine, which has been integrated in Japanese medical system and people's life; Watanabe et al 2001), massage and acupuncture.…”
Section: Self-care In the Context Of Anti-ageing Medicinementioning
confidence: 87%
See 1 more Smart Citation
“…Self-care was defined-in line with established research definitions (Mun et al 2016;Adams et al 2018)-as the self-determined and self-administered use of products or practices for addressing health problems and/or maintaining health practiced by individuals without instruction from healthcare professionals. Details of the search criteria can be found in the Additional file 1.…”
Section: Search Designmentioning
confidence: 99%
“…Varying definitions of self-care are rapidly emerging, in tandem with a trend toward patient-centered health care and an increase in chronic over acute, conditions (Mun et al 2016). Here, we define self-care as the self-determined and self-administered use of products or practices for addressing health problems and/or maintaining health practiced by individuals without instruction from healthcare professionals in line with established research definitions (Mun et al 2016;Adams et al 2018). Both complementary and alternative medicine (CAM) self-care (e.g.…”
Section: Introductionmentioning
confidence: 99%